2018
DOI: 10.1108/md-11-2016-0826
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of regulatory focus and institutions on innovation

Abstract: Purpose Many factors influence entrepreneurs, some of which influence the level of innovation (i.e. innovative or imitative) of new products or services pursued. The purpose of this paper is to explore the impact of the psychological motivations of the entrepreneurs and their institutional setting on the innovativeness of the new venture they pursue. Through this exploration, we can gain a better understanding of how innovative new ventures still occur in varying institutional environments. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 109 publications
1
12
0
1
Order By: Relevance
“…Chadee and Roxas (2013) suggested that the current state of formal institutions in the form of regulatory quality, rule of law and corruption inhibit firm innovation and performance in Russia. Cowden and Bendickson (2018) noted that different institutional environments are interconnected with the regulative, cognitive and normative behavior of individuals, where national institutions may influence the relationship between the cognitive motivations of entrepreneurs and the innovativeness of new ventures.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Chadee and Roxas (2013) suggested that the current state of formal institutions in the form of regulatory quality, rule of law and corruption inhibit firm innovation and performance in Russia. Cowden and Bendickson (2018) noted that different institutional environments are interconnected with the regulative, cognitive and normative behavior of individuals, where national institutions may influence the relationship between the cognitive motivations of entrepreneurs and the innovativeness of new ventures.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Individuals operating primarily with promotion focus are concerned about accomplishments, hopes, and aspirations and pursue an “ideal self” (Kark and Van Dijk, 2007). They are likely to exhibit “exploratory” behaviors (Förster et al, 2004) and to be more open to creativity and innovation (Cowden and Bendickson, 2018). Neubert et al (2008) found a positive relationship between promotion focus and helping and creative behaviors, while Lanaj et al (2012) proposed that promotion focus was associated with innovation.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Meanwhile, China has also greatly strengthened its innovation-related regulations, including intellectual property rights (IPR) legislations, technical and product standards, and environmental regulations (Mangelsdorf, 2011;Zhao and Sun, 2016;Peng et al, 2017). In such a dynamic institutional environment, Chinese firms' innovation is shaped not only by the firm-specific resources, but also by the above institutional conditions and transitions (Peng et al, 2009;Cowden and Bendickson, 2018).…”
Section: Introductionmentioning
confidence: 99%